Language and Learning in the Digital Age, James Paul Gee and Elisabeth R. Hayes. London: Routledge, 2011, 159 pages. ISBN: 9780415602778 - Jyh Wee Sew, (Kajian Malaysia, 2015)
While the authors Gee and Hayes accord a secondary status to written as compared to oral literacy, both types of literacy are nonetheless defined as continuums of a language delivery system (p. 15). In the digital age, learning necessarily includes expert collaboration via the use of digital technology. Interaction in spaces such as chat channels, whispers, group chats, friend lists, guilds and guild chats (cf. Dickey, 2011) requires constant conversation between online users (cf. Steinkuehler and Williams, 2006). Similar to the diverse interactions that occur in multiplayer online games (MMO), exchanges in digital media with the opportunity for learning are prevalent across a spread of digital tools.